Variation Over Time and Factors Associated With Detection Rates of Sessile Serrated Lesion Across the United States: Results Form a National Sample Using the GIQuIC Registry. (21st January 2021) - Shaukat, Aasma; Holub, Jennifer; Greenwald, David; Eisen, Glenn; Schmitt, Colleen
Abstract : INTRODUCTION: Sessile serrated lesions (SSLs) are important precursor lesions for the CpG island–methylated pathway to colorectal cancer. The reported detection rates of SSL are highly variable, and national or population-based estimates are not available. Patient-, provider-, and procedure-level factors associated with the detection rates of SSL have not been well described. The aim of our study was to study the detection rates of SSL, variability of rates over time, and factors associated with detection rates of SSL in a national sample of patients undergoing colonoscopy using the GIQuIC registry. METHODS: We used colonoscopies submitted to the GIQuIC registry from 2014 to 2017 on adults, aged 18–89 years. Only the first colonoscopy record per patient was included. Indications for colonoscopy were categorized as screening, diagnostic, and surveillance. We used the hierarchical logistic models to study the factors associated with the detection rates of SSL. The Cochrane-Armitage test was used to study the significance of trend over time. RESULTS: There were a total of 5, 173, 211 colonoscopies performed by 3, 934 endoscopists during the study period. Among the 2, 101, 082 screening colonoscopies over the study period in adults older than or equal to 50 years that were complete to the cecum, the average detection rate per endoscopist for SSL was 6.43% (SD 5.18) and 6.25% standardized for the 2010 US population. There was a significant increase in the detection rates of SSLs from screening colonoscopies over the study period from 4.99% in 2014 to 7.09% in 2017 ( P trend <0.001). Clinically significant factors associated with higher detection rates of SSL were longer withdrawal times (>11 minutes vs ≤6 minutes) (odds ratio [OR] 9.61; 9.03–10.24), adequate preparation (OR 1.25; 1.22–1.28), female sex (OR 1.17; 1.16–1.18), and use of a specialized gastrointestinal pathology group (OR 1.12; 95% confidence interval 1.04, 1.19). DISCUSSION: Population-based estimates of the detection rates of SSL are 6% and have increased over time.